971 Gamification of Education; Can Playable Education Result in Better Learning Outcomes?. (19th August 2022) - Badenoch, T; Benton, K; Jacobs, E; Curtis, A; Law, S; Everett, S; Ahmed, M; Hunter, I; Bamford, R
Abstract: Aim: Combining traditional simulation (TS) and the emerging field of gamification, to create medical Escape Rooms (ERS) has been used in Nursing to good results but is yet to be widely adopted in medical education. We conducted a pilot study to create ERS for undergraduates to assess their educational value. Method: Existing Simulation themes of sepsis, post-operative bleeding, trauma, burns and communication in the theatre environment were developed into Escape Rooms by a multidisciplinary team. A cross over study for 4 th year students was carried out. Questionnaires were used to evaluate the experience, learning assessed by pre and post quiz and observational tools for teamwork, communication and leadership were utilised. Results: Qualitative data demonstrated overall good feedback on enjoyment an engagement. Quantitative data collected as pre- and post-exposure learning demonstrated equivocal benefit. Self-assessed teamwork showed equal in all domains and improved in contribution of knowledge and maintaining team focus on the ER group. Conclusions: Participants find ER enjoyable have similar educational benefits of traditional simulation with the benefits on enhancing non-technical skills amongst a novice group. Escape rooms may be useful as an adjunct to TS particularly at developing non-technical skills.